(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article describes the views of Jalaluddin Rumi on the human psyche, the psychological aspects of his scientific heritage, and also presents the interpretation of the emotional states of a person, described in the works "Masnaviyi manaviyi" and "Fihi ma fihi".